Research of the occupational risk at workplaces of workers with disabilities - Danova, Karyna; Malysheva, Viktoriya; Bogatov, Оleg; Chencheva, Оlha (Social Development and Security, 2020)
The social orientation of business is a modern global trend, in which corporations pay more attention to the social, environmental aspects of their activities, trying to reduce the negative influence of business processes on the environment and increase the level of social safety. This approach is implemented including the involvement to the workplaces the representatives of socially vulnerable groups, in particular, people with disabilities, as well as creating appropriate and safe working conditions for all workers at the workplace. At the same time, special attention should be paid to the organization of occupational safety of vulnerable groups, in particular, people with disabilities, which are an extremely important element in improving the effectiveness of the overall safety management system at the enterprise.The scientific article is devoted to the topical issue of improving the level of safety at the workplaces of workers with disabilities by developing methodological frameworks for hazard identification and risk assessment at the enterprise based on the analysis of the international standard DSTU IEC / ISO 31010: 2013, and the Project of carrying out by employer the occupational health and hygiene measures based on a risk-oriented approach. The employer, as the person who is legally responsible for ensuring an adequate level of safety at the workplace, is interested in implementation the effective preventive measures to prevent accidents and occupational diseases, and the risk-based approach is recognized as the most effective way to achieve this goal. The article analyzes the algorithms of the procedure for assessing occupational risks and proposes an approach to grouping risks based on the nature of the influence on the employee, place of origin, as well as environmental impact, which allows adapting the procedure to risk assessment at the workplace of different groups of workers and take into account the different conditions of persons who are directly involved in the production process.